2020
DOI: 10.24036/0202094111941-0-00
|View full text |Cite
|
Sign up to set email alerts
|

Stress and anxiety among adolescents, during the covid-19 outbreak

Abstract: Covid-19 affects every aspect of human life, especially psychological aspects. Furthermore, adolescents experience difficulties because of the pandemic and therefore require extra change due to the occurring situation. In this situation, adolescents felt stress from having to adjust to the unpredictable situation, as well as anxiety, from facing an uncertain situation. Meanwhile, from the previous year, the news has been updated daily, concerning the number of deaths and positive cases. Teens are able to acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Furthermore, a study conducted in Sri Lanka among 445 adolescents aged 14-18 years found that the prevalence of severe anxiety was 28% [15]. In addition, during the COVID-19 pandemic, an increase in the prevalence of adolescence anxiety has been observed around the world [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study conducted in Sri Lanka among 445 adolescents aged 14-18 years found that the prevalence of severe anxiety was 28% [15]. In addition, during the COVID-19 pandemic, an increase in the prevalence of adolescence anxiety has been observed around the world [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This can be because adolescences are having a hard time because of the sudden changes. In these situations, they feel stressed and anxious because they have to adjust to uncertain situations 11 . In addition, school closures and prolonged quarantine at home also have a negative impact on adolescent mental health 12 .…”
Section: Introductionmentioning
confidence: 99%
“…This emotion arises in anticipation of future threats and is often associated with muscle tension, alertness to future threats, and avoidant behavior (APA, 2013). Anxiety is prone to be experienced by adolescents (Fitria & Ifdil, 2020;Ifdil et al, 2021). The Institute of Health Metrics (IHME) Global Burden of Disease in 2018 reported that the coverage of the prevalence of anxiety disorders in adolescents aged 15-19 years globally reached 4.60% (Dattani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The results of a study on 380 adolescents in Indonesia showed that as many as 58.74% of adolescents experienced anxiety problems during the COVID-19 pandemic (Pertiwi et al, 2021). In addition, anxiety problems in adolescents during the COVID-19 pandemic were found to be at an alarming level (Ifdil et al, 2021), likely due to the inequality between adolescent capacity and environmental demands to make quite extreme adjustments in the midst of the COVID-19 pandemic (Guessoum et al, 2020). The COVID-19 situation, which is considered threatening to physical and psychological health, as well as changing the dynamics of daily life, triggers anxiety symptoms in adolescents and gives rise to various problems, such as sleep problems (lack of sleep or insomnia), concentration and memory problems (frequent forgetting), and emotional stability problems (irritability or provoked by negative emotions) (Fitria & Ifdil, 2020).…”
Section: Introductionmentioning
confidence: 99%